Molecular and histopathological detection of rabbit hemorrhagic disease virus in young rabbits - EL-Nahas, E. M. (2011)
Calicivirus infection causes rabbit haemorrhagic disease (RHD) that kills more than 90% of adult animals, whereas young rabbits are naturally resistant to this viral disease. Interestingly, we have detected rabbit haemorrhagic disease virus (RHDV) in liver and intestinal tissues from suddenly died young rabbits (5-6 weeks old) in a remote private farm at Tukh, Kaluobia. Preliminary detection using haemagglutination (HA) test revealed a higher titer ofHA antigen 27 and 2p8 (Bin liver and intestine respectively using type 0 human erythrocytes. A genomic region encoding the capsid protein (VP60) within RHDV was identified by Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). The amplified cDNA gives size of approximatrly 538 bp. Also Liver and intestinal homogenates reacted positively by haemagglutination (HA) assays to different human blood groups (0, A, S, and AS) at 4 DC. Experimentally RHDV detected strain appears likely to be of high pathogenicity to young rabbits rather than adult. Histopathological examination showed acute necrotizing hepatic necrosis and crypt necrosis in the intestine. We conclude that a new RHDV strain infecting young rabbits (5-6 weeks old) was circulated and further characterization of the strain was requireds
Includes references.
Summary in Arabic.
1
Keywords: Hemorrhagic diseases; Rabbits -- Diseases